The Effect of Affiliate Needs Towards Cybersex on Male Adolescent Users of Online Dating Application (Sains Humanika, 2021)
When it blooms once the use of applications dating online, who used male adolescents to mutually acquainted and interact with your opponent types, online dating application users initially only craved having a relationship with someone else, however, the passage of time of application of dating online is not only used as a place to get acquainted but to do cybersex. The research is aimed to know how to influence the needs of affiliates against cybersex on a male adolescent who used the application of dating online. Subject research, as much as 42 male adolescents who used the form of dating online, aged 18-40 years old, method of analysis is using methods quantitative. Collecting the data in the study is using a scale Likert, namely the scale of the needs of affiliates, with the reliability of 0.902 and scale cybersex with a coefficient of reliability of 0. 816. Analysis of the data used is a test of linear regression simple, earned value F of 0.403 and Sig = 0,000 (P> 0.001), it can be concluded that the need for affiliation has no effect on cybersex.  The coefficient of determination (R Square) of 0. 042, which has a meaning that influences the need of affiliates against cybersex, amounted to 4.2 %.
Keywords: Applications Dating Online; Cybersex, Needs Affiliate